2010
DOI: 10.1159/000315155
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Macular Edema

Abstract: Macular edema is defined as an accumulation of fluid in the outer plexiform layer and the inner nuclear layer as well as a swelling of Müller cells of the retina. It consists of a localized expansion of the retinal extracellular space (sometimes associated with the intracellular space) in the macular area. Macular edema is a common cause of a sudden or chronic decrease in visual acuity occurring in many ocular diseases such as age-related macular degeneration, diabetic retinopathy and retinal vein occlusion. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 31 publications
1
102
0
16
Order By: Relevance
“…Swelling of Müller cells due to disturbed fluid transport has been described in states of macular edema [88,89]. We believe, through combining UHR OCT and adaptive optics and thereby increasing image resolution, demonstration of in vivo morphological changes of Müller cells could unveil new information on the pathogenesis of uveitic macular edema.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 87%
“…Swelling of Müller cells due to disturbed fluid transport has been described in states of macular edema [88,89]. We believe, through combining UHR OCT and adaptive optics and thereby increasing image resolution, demonstration of in vivo morphological changes of Müller cells could unveil new information on the pathogenesis of uveitic macular edema.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 87%
“…Since the eye also could be a potential biomarker for systemic changes related to diabetes [33], improved retinal imaging is of great significance. The spectrum of neurovascular damage is a consequence of a failure of glycemic control, with consequent microvascular damage and resulting hypoxia [34][35][36][37][38][39]. Diabetic retinal vascular abnormalities seen in early to moderate NPDR include pericyte loss, basement membrane thickening, arteriole wall thickening, and microaneurysm formation.…”
Section: Introductionmentioning
confidence: 99%
“…These signs of diabetic retinopathy, the hard exudates, NVD and NVE, are quite evident using traditional imaging techniques. However, the earlier vascular changes such as IRMA and capillary nonperfusion [22,[35][36][37]39] are not always evident clinically. With the development of novel therapies and interventions for diabetic control, there is a growing importance for monitoring the early stages of diabetic retinopathy [33].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage is accompanied by complex cellular and inflammatory reactions, which include vascular dysfunction, damage to the blood-retinal barrier, and release of several angiogenic and inflammatory mediators. 5 The balance of angiogenic and inflammatory mediators has been reported to be disturbed in the ocular fluid in RVO. [6][7][8][9] Previous reports showed no correlation between cytokine levels in the aqueous humor and plasma 7,10 : thus, providing evidence that the source of these cytokines is intraocular.…”
mentioning
confidence: 99%
“…Hypoxia causes increased expression of VEGF, a potent mediator of vascular permeability, which causes vascular leakage. 5 Several studies have demonstrated the efficacy of intravitreally injected anti-VEGF agents, for example, bevacizumab (IVB), for treatment of ME caused by RVO. 14,15 Many studies have evaluated the profiles of various cytokines in intraocular fluid, 10,16 the relationship between intraocular cytokine levels and macular edema, 7,17 and the association between cytokine concentrations and the effect of anti-VEGF therapy 18,19 in RVO patients.…”
mentioning
confidence: 99%